Phyllospheric Microbial Composition and Diversity of the Tobacco Leaves Infected by Didymella segeticola - Huang, Yu; Wang, Han-Cheng; Cai, Liu-Ti; Li, Wenhong; Pan, Daiwei; Xiang, Ligang; Su, Xiankun; Li, Zhong; Adil, Muhammad Faheem; Shamsi, Imran Haider (Frontiers in Microbiology, 2021)
Myriad of biotic and abiotic factors inevitably affect the growth and production of tobacco (Nicotiana tabacum L.), which is a model crop and sought-after worldwide for its foliage. Among the various impacts the level of disease severity poses on plants, influence on the dynamics of phyllospheric microbial diversity is of utmost importance. In China, recurring reports of a phyto-pathogen, Didymella segeticola, a causal agent of tobacco leaf spot, accentuate the need of its in-depth investigation. Here, a high-throughput sequencing technique, IonS5TMXL was employed to analyze tobacco leaves infected by D. segeticola at different disease severity levels, ranging from T1G (least disease index) to T4G (highest disease index), in an attempt to explore the composition and diversity of phyllospheric microbiota. In all healthy and diseased tobacco leaves, the most dominant fungal phylum was Ascomycota with high prevalence of genus Didymella followed by Boeremia, Meyerozyma and Alternaria, whereas in case of bacterial phyla, Proteobacteria was prominent with Pseudomonas being a predominant genus, followed by Pantoea. The relative abundance of fungi, i.e., Didymella and Boeremia (Ascomycota) and bacteria, i.e., Pseudomonas and Pantoea (Proteobacteria) were higher in diseased groups compared to healthy groups. Healthy tissues exhibited quite rich and diverse fungal communities in contrast with diseased groups. The infection of D. segeticola had a complex and significant effect on fungal as well as bacterial alpha-diversity. FUNGuild analysis indicated that the relative abundance of pathotrophs and saprotrophs in diseased tissues proportionally increased with disease severity. PICRUSt analysis of diseased tissues indicated that the relative abundance of bacterial cell motility and membrane transport related gene sequences elevated with an increase in disease severity from T1G to T3G and then tended to decrease at T4G. Conclusively, the current study shows the typical characteristics of tobacco leaf microbiome and provides insights into the distinct microbiome shifts on tobacco leaves infected by D. segeticola.